KREATIVITAS COOK DALAM TEKNIK FOOD PLATING DI RESTORAN HOTEL ALPHA PEKANBARU - Gita Novianti; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Alpha Hotel under the management of Satu Enam Delapan Bersama Company which was established on February 27, 2012 and recorded in AKTA Number 45, was legalized at the notary office of Sutrisno Arsjad, S.H but began operating as of December 14, 2013. This hotel is a branch of Alpha Inn Hotel located in Medan City, North Sumatra. Alpha Hotel Pekanbaru is located in a very strategic location on Jalan Haji Imam Munandar No. 17, guests can not only expect easy access to the hotel, but can also reach all locations in Pekanbaru easily, including places such as shopping centers, various tourist sites, recreational locations, and only about 10 to 15 minutes from the airport International Sultan Syarif Kasim II Pekanbaru. The importance of a cook's creativity in the food plating technique is very influential on the quality of the food served in order to attract and add to the customer's interest when consuming it. This research was conducted to determine the creativity of a cook in food plating techniques. This study uses qualitative methods, while data collection techniques in this study use observation, in-depth interviews, and documentation. The key informants in this study were 3 cook employees. Based on the results of research conducted, for the overall interview results said that the creativity of cook in food plating techniques in theRestaurants of Alpha Hotel Pekanbarustill need to improve and maintain the quality that they have.Keywords: Creativity, Cook, Food Plating, Restaurant.